Reaping the fruits of collaboration: learning development research in the LearnHigher CETL network - Kim Shahabudin (Association for Learning Development in Higher Education (ALDinHE), 2009)
The LearnHigher CETL is now is in its fourth year of developing research-informed resources to support student learning development. Partners at 16 UK Higher Education institutions have amassed a large quantity of data from students and staff on their preferences, needs and practices in twenty learning areas, as well as information about the use and design of learning spaces, and the role of learning developers. This article will report on LearnHigher's collaborative approach, using examples from a report to be published in Spring 2009 which takes an overview of LearnHigher research.